2013
DOI: 10.1038/ejhg.2013.88
|View full text |Cite
|
Sign up to set email alerts
|

Prospective diagnostic analysis of copy number variants using SNP microarrays in individuals with autism spectrum disorders

Abstract: Copy number variants (CNVs) have repeatedly been found to cause or predispose to autism spectrum disorders (ASDs). For diagnostic purposes, we screened 194 individuals with ASDs for CNVs using Illumina SNP arrays. In several probands, we also analyzed candidate genes located in inherited deletions to unmask autosomal recessive variants. Three CNVs, a de novo triplication of chromosome 15q11-q12 of paternal origin, a deletion on chromosome 9p24 and a de novo 3q29 deletion, were identified as the cause of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 49 publications
3
56
0
1
Order By: Relevance
“…Deletion and duplication cause microcephaly and macrocephaly, respectively, and schizophrenia is only one of many associated neurodevelopmental phenotypes [54]. The 3q29 deletion was first described to cause mental retardation, with slight dysmorphic facial features [55] and in some cases autism [56] and was later linked to schizophrenia [57-59]. The 7q11.23 duplication is reciprocal to the Williams-Beuren syndrome deletion [60] and in addition to schizophrenia has been associated with autism, language delay, and mental retardation [61].…”
Section: High-penetrance Genetic Variationmentioning
confidence: 99%
“…Deletion and duplication cause microcephaly and macrocephaly, respectively, and schizophrenia is only one of many associated neurodevelopmental phenotypes [54]. The 3q29 deletion was first described to cause mental retardation, with slight dysmorphic facial features [55] and in some cases autism [56] and was later linked to schizophrenia [57-59]. The 7q11.23 duplication is reciprocal to the Williams-Beuren syndrome deletion [60] and in addition to schizophrenia has been associated with autism, language delay, and mental retardation [61].…”
Section: High-penetrance Genetic Variationmentioning
confidence: 99%
“…This function of Caspr2 in neural development is comparable to the involvement of the neural cell-adhesion molecules contactin 4, contactin 5 and contactin 6 in brain development [Mercati et al, 2013]. Disruptions in these contactin genes confer an increased risk for ASD [van Daalen et al, 2011;Nava et al, 2014]. Likewise, loss of Caspr2 function may contribute to the ASD found in several patients with CNVs in CNTNAP2 [Zweier et al, 2007;Alarcon et al, 2008;Poot et al, 2010].…”
Section: Expression Evolutionary Conservation and Functions Of Cntnap2mentioning
confidence: 81%
“…Several Contactins have also been implicated in the control of neuronal migration, although this function may be partially due to their effects on neuronal proliferation and differentiation (Denaxa et al, 2005;Ma et al, 2008;Wang et al, 2011;Xenaki et al, 2011). Similarly, both APP and Contactins have been linked with a variety of neurodevelopmental and age-related disorders: genetic mutations affecting Contactin-3, Contactin-4, Contactin-5, and Contactin-6 are strongly associated with autism spectrum disorders (ASDs; Zuko et al, 2013;Mohebiany et al, 2014;Nava et al, 2014;Hu et al, 2015), while elevated sAPP levels have been identified as potential biomarkers for the most severe forms of ASD (Sokol et al, 2006;Ray et al, 2011).…”
Section: Contactin-app Signaling In Both Development and Diseasementioning
confidence: 99%
“…It has been postulated that an authentic APP ligand might stimulate the proteolytic cleavage of the holoprotein by one or more secretases (O'Brien and Wong, 2011;Zheng and Koo, 2011). Accordingly, we also tested whether treating embryos with MsCont-Fc altered the relative abundance of full-length or cleaved forms of APPL (quantified by our Western blotting methods).…”
Section: Complementary Binding Of Appl and Contactin Fusion Proteins mentioning
confidence: 99%